Islamic Religious Education in Bosnia and Herzegovina Maktabs through the Prism of Mu'allims - Sijamhodžić-Nadarević, Dina; Čolić, Ahmed (Nazhruna: Jurnal Pendidikan Islam, 2023)
This article aims to highlight the core educational/upbringing processes of Islamic Religious Education in Bosnia and Herzegovina maktabs, based on the theoretical framework and qualitative research using interview methods. A short framework of the development and status of maktabs in Bosnia and Herzegovina as basic nonformal institutions of Islamic education among Muslims is provided in the introduction. The aim of the research is to examine the attitudes and experiences of muallims regarding the possibilities of realizing the fundamental areas of religious education/upbringing, and the use of approaches, methods, and forms of religious education of children in maktabs. This part of the research also aims to examine the perceptions of muallims about the importance of the principles of religious upbringing of children. The findings show that through methodical/didactical religious education work with children, it is possible to develop all areas of education and that this process runs simultaneously, building a complete personality of the child. It is also apparent that muallims respect the basic educational principles, with a note that the certain educational principles are difficult to fully implement due to numerous limitations. When it comes to educational approaches and methods, it is evident that the prevalent approach is directed towards positive transformation and the encouragement of pupils, which stimulates the internalization of universal and Islamic values.